Determinants of Sovereign Bond Spreads in Emerging Markets : Local Fundamentals and Global Factors vs. Ever-Changing Misalignments - Csonto, Balazs (IMF Working Papers; Working Paper, 2013)
We analyze the relationship between global and country-specific factors and emerging market debt spreads from three different angles. First, we aim to disentangle the effect of global and country-specific developments, and find that while both country-specific and global developments are important in the long-run, global factors are main determinants of spreads in the short-run. Second, we investigate whether and how the strength of fundamentals is related to the sensitivity of spreads to global factors. Countries with stronger fundamentals tend to have lower sensitivity to changes in global risk aversion. Third, we decompose changes in spreads and analyze the behavior of explained and unexplained components over different periods. To do so, we break down fitted changes in spreads into the contribution of country-specific and global factors, as well as decompose changes in the residual into the correction of initial misalignment and an increase/decrease in misalignment. We find that changes in spreads follow periods of tightening/widening, which are well-explained by the model; and the dynamics of the components of the unexplained residual follow all the major developments that impact market sentiment. In particular, we find that in the periods of severe marketstress, such as during the intensive phase of the Eurozone debt crisis, global factors tend to drive changes in the spreads and the misalignment tends to increase in magnitude and its relative share in actual spreads.